PENGEMBANGAN APLIKASI SMART TOUR SUGGESTION KOTA YOGYAKARTA BERBASIS WINDOWS PHONE - , NICO DARMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta, a city known for its diversity of tourist destinations, be it nature, culture, and culinary. With a name like that, so the city is always visited by local and foreign tourists. By looking that potential, Yogyakarta need a tour guide who can easily provide information on tourist sites, transportation routes, costs and the estimated time for the tourists. Mobile phone industry is one industry that is growing very fast. One of the most popular today is the smartphone operating system in which there is one - each like a PC / Laptop. This research developed a tour guide application that can be accessed through a mobile phone based on Windows Phone. From this study produced a Smart Tour Suggestion application based on Windows Phone, that can display a map, which can be accessed offline to provide a way information, the location and directions to tourist attractions in Yogyakarta and surrounding areas This application is expected to provide information about travel and placeâs support to provide information about who is considered to be less for tourists in the Yogyakarta area.